Exploring the impact of expert guidance from school-based mentors on student teachers' professional learning. Issue 1 (2nd January 2022) - Forster, Colin; Wire, Tracey; Eperjesi, Rachel; Hollier, Ruth; Howell, Emma; Penny, Jude
ABSTRACT: This article reports on research undertaken to understand the impact on primary student teachers' professional learning when school-based mentors explicitly share their expertise through discussing some of the 'Learn how to' statements from the Core Content Framework for Initial Teacher Training, introduced by the Department of Education in 2019 to establish minimum entitlement for all student teachers. Initial Teacher Education has become more school-based and the role of school-based mentors is increasingly significant. Primary student teachers took part in an online survey, and school-based mentors in focus group discussions, to explore the impact of weekly expert guidance meetings and how these might be improved. Student teachers valued learning from school-based mentors when they shared their expertise in an explicit, well-contextualised way but this practice was not fully embedded across schools. Mentors were keen to share their expertise with student teachers, and identified the importance of structured, dedicated time to discuss the 'learn how to' statements, tailored to individual needs, and for student teachers to identify specific follow-up actions to apply to their developing practice. Mentors identified ways in which such discussions might have greater impact through, for example, developing their knowledge of the curriculum of the ITE provider.